1998
DOI: 10.1021/jp9826367
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Spectroscopic Investigation of Molecular Structures of Highly Dispersed Vanadium Oxide on Silica under Various Conditions

Abstract: The molecularly dispersed V 2 O 5 /SiO 2 supported oxides were prepared by the incipient wetness impregnation of 2-propanol solutions of V-isopropoxide. The experimental maximum dispersion of surface vanadium oxide species on SiO 2 was achieved at ∼12 wt % V 2 O 5 (∼2.6 V atoms/nm 2 ). The surface structures of the molecularly dispersed V 2 O 5 /SiO 2 samples under various conditions were extensively investigated by in situ Raman, UVvis-NIR DRS and XANES spectroscopies. The combined characterization techniques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

53
503
1
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 354 publications
(558 citation statements)
references
References 59 publications
53
503
1
1
Order By: Relevance
“…nH 2 O gel-like structure. The blue-shift of the band at 1023 cm )1 can be explained by the variation of the water content n in the gel [27]. In the same study it has been shown, that the variation of the water content in the gel can also lead to the presence of an additional band at $915 cm )1 , which has been attributed to the stretching of V@O double bond coordinated with water.…”
Section: Reactivity Behavior During Methanol Oxidationmentioning
confidence: 73%
See 2 more Smart Citations
“…nH 2 O gel-like structure. The blue-shift of the band at 1023 cm )1 can be explained by the variation of the water content n in the gel [27]. In the same study it has been shown, that the variation of the water content in the gel can also lead to the presence of an additional band at $915 cm )1 , which has been attributed to the stretching of V@O double bond coordinated with water.…”
Section: Reactivity Behavior During Methanol Oxidationmentioning
confidence: 73%
“…[22] and Mg 3 V 2 O 8 [23,24]. Also, the corresponding Raman spectra are dominated by a band at 1040 cm )1 (see inset), which has been assigned to isolated tetrahedral VO 4 with three V-O support bonds and one V@O bond in the literature [25][26][27][28][29]. It should be mentioned, that recent studies have challenged the above assignment [30,31].…”
Section: Synthesis Of Vo X /Sba-15mentioning
confidence: 99%
See 1 more Smart Citation
“…[3] Apparently, variations in the vanadium oxide loading, support oxide and measurement conditions complicate the determination of the molecular structure of hydrated supported vanadium oxide catalysts making use of X-ray absorption spectroscopy. Although clustering of vanadium oxide species upon hydration of the sample has often been suggested, [4,8,18,19] only a limited number of research groups have investigated the presence of vanadium atoms in the second coordination shell. [14,20] Silversmit et al detect additional cations in their hydrated sample (CN = 2, R = 3.5 Å), however, they were not able to distinguish between the support cation (Ti) and a neighbouring vanadium atom.…”
Section: Introductionmentioning
confidence: 99%
“…A large extent of hydration of the catalyst under ambient conditions is also apparent from the UV-Vis spectrum of the catalyst, shown as an insert in Figure 1. The assignments of the absorption bands in the UV-Vis spectrum are discussed in detail elsewhere [6,7]. Changes in the Infrared spectrum upon dehydration, induced by evacuation to 100 mTorr, are shown in the difference spectrum Figure 1b.…”
Section: Layer Deposition and Introduction Of Cyclohexenementioning
confidence: 99%